Seasonal Variation and Sexual Dimorphism of the Microbiota in Wild Blue Sheep (Pseudois nayaur) - Zhu, Zhaoling; Sun, Yewen; Zhu, Feng; Liu, Zhensheng; Pan, Ruliang; Teng, Liwei; Guo, Songtao (Frontiers in Microbiology, 2020)
Microbiota of the wild blue sheep (Pseudois nayaur) presents a seasonal variation due to different dietary selection and feeding strategies from different ecological niches chosen by different sex in summer. To address those issues, we analyzed the variation of gut microbiota based on the material from the feces, with 16S rRNA and meta-genome aimed to explore seasonal and gender differences. The results indicate that seasonal dietary changes and gender differentiation, as expected, cause the variation in sheep’s gut microbiota structure. The variation of the former is more significant than the latter. Dominant Firmicutes exists a significantly higher abundance in summer than that in winter. Subordinate Bacteroides expresses no seasonal difference between the two seasons. Compared with the winter group, the summer group is featured by abundant enzymes digesting cellulose and generating short-chain fatty acids (SCFAs), such as beta-glucosidase (EC: 3.2.1.21) for cellulose digestion, and butyrate kinase (EC:2.7.2.7) in butyrate metabolism, implying that the changes of the composition in intestinal flora allow the sheep to adapt to the seasonalized dietary selection through alternated microbial functions to reach the goal of facilitating the efficiency of energy harvesting. The results also show that the blue sheep expresses a prominent sexual dimorphism in the components of gut microbiota, indicating that the two sexes have different adaptations to the dietary selection, and demands for physical and psychological purposes. Thus, this study provides an example of demonstrating the principles and regulations of natural selection and environmental adaptation.